Influencer Marketing and Purchase Intention of Local Sportswear: The Mediating Role of Brand Awareness - Rizkia Fajar Eka Putro; Agus Aribowo (International Journal of Multidisciplinary Sciences and Arts, 2026)
The rising popularity of sports in Indonesia contributed to rapid advancement in the domestic sportswear sector, leading to heightened market competitiveness. Brands need to utilize successful digital marketing strategies, including influencer marketing, to maintain competitiveness in this dynamic environment. This study seeks to examine the impact of influencer marketing on consumer purchase intention for local sportswear products, with brand awareness serving as a mediating variable. The study utilized a quantitative methodology using a cross-sectional survey with 200 participants selected via purposive and snowball sampling methods, focusing on individuals familiar with local sportswear brands involved in influencer collaborations. Data were analyzed utilizing SPSS and SmartPLS. The findings demonstrate that influencer marketing significantly enhances brand awareness (0.680) and exerts a notable direct influence on purchase intention (0.378). Moreover, brand awareness substantially affects the correlation between influencer marketing and purchase intention (0.365), indicating that influencers stimulate transactional desire by initially fostering brand familiarity. The structural model exhibits substantial explanatory power, explaining 70.7% of the variance in purchase intention. For local enterprises, these findings indicate that choosing trustworthy and relevant influencers is crucial for cultivating genuine relationships and augmenting consumer trust. In conclusion, the study indicates that cultivating brand awareness is an essential approach for effective influencer marketing. Future research could investigate further mediating variables, such as content quality or customer demographics, to yield more profound insights into the determinants of local sportswear consumption.